The New Yorker : stories - Beattie, Ann. (New York : Scribner, 2010)
Collects every Beattie story published in "The New Yorker" magazine throughout a thirty-five-year period, in an anthology that offers insight into modern American family life.
A platonic relationship -- Fancy flights -- Wolf dreams -- Dwarf house -- Snake's shoes -- Vermont -- Downhill -- Wanda's -- Colorado -- The lawn party -- Secrets and surprises -- Weekend -- Tuesday night -- Shifting -- Distant music -- A vintage Thunderbird -- The Cinderella waltz -- The burning house -- Waiting -- Greenwich time -- Gravity -- Running dreams -- Afloat -- Girl talk -- Like glass -- Desire -- Moving water -- Coney Island -- Television -- Lofty -- One day -- Heaven on a summer night -- Times -- In the white night -- Summer people -- Janus -- Skeletons -- Where you'll find me -- Home to Marie -- Horatio's trick -- Second question -- Zalla -- The women of this world -- That last odd day in L.A. -- Find and replace -- The rabbit hole as likely explanation -- Coping stones -- The confidence decoy.
Complete collection of the author's stories previously published in The New Yorker, 1974-2006.
Keywords: New York (N.Y.) -- Fiction; Short stories